PELAKSANAAN KOMPETENSI PROFESIONAL GURU PAI DALAM PENINGKATAN EFEKTIVITAS BELAJAR PESERTA DIDIK DI SMAN 3 JOMBANG - Ali Mustofa (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2019)
Implementation of PAI teacher professional competence is the ability or expertise of a teacher in carrying out obligations responsibly and properly. Competencies possessed by each PAI teacher will show the quality of the teacher in teaching. The competence will be realized in the mastery of knowledge and professional in carrying out its function as a teacher. PAI teachers are required to have competence in order to foster the personality (character) of students. PAI teacher's task of the learning process must have the ability to manage student learning effectiveness activities through approaches and methods used in achieving goals. This is evidenced by the role and function of PAI teacher professional competence by taking into account the supporting and inhibiting factors in the learning process of PAI. The results of the study show that the implementation of PAI teacher's professional competence in improving the learning effectiveness of students at Senior High School of 3 Jombang is proven by the implementation of professional competence and the task of PAI teachers in teaching and learning activities through strategies, approaches, methods, media and evaluation of learning. So that the learning effectiveness of students is well controlled, with other evidences the students are focused on the material delivered by the teacher, as well as the active role of students when answering questions given by the teacher. Then the teacher gives one example of social experimentation to students then practiced by these students.